(untitled) (Journal of Engineering, 2016)
This paper presents experimentally a new configuration of shear connector for Steel-Concrete-Steel (SCS) sandwich beams that is derived from truss configuration. It consists of vertical and inclined shear connectors welded together and to cover steel plates infilled with concrete. Nine simply supported SCS beams were tested until the failure under a concentrated central load (three- point bending). The beams were similar in length (1100mm), width (100mm), and the top plate thickness (4mm). The test parameters were; beam thickness (150, 200, 250, and 300mm), the bottom plate thickness (4, and 6mm), the diameter of the shear connectors (10, 12, and 16mm), and the connector spacing (100, 200, and 250mm). The test results showed that the stiffness of SCS beam augmented with the increase in beam thickness, lower plate thickness, and connector diameter while it decreased with increasing the connector spacing. The ultimate load capacity of the SCS beams increased to 72.2% and 42.1% by enlarging the beam thickness and connector diameter to 100% and 60%, respectively. Increasing the connector spacing of 150% led to a considerable reduction in the ultimate load reached to 68.4%. Finally, the ultimate strength was not affected by augmenting the bottom plate thickness up to 50%.